Role of the AV3V region in the pressor responses induced by amygdala stimulation - (:unkn) unknown (ELSEVIER SCIENCE BV, 1997)
The role of the anteroventral third ventricle (AV3V) region in the presser responses to carbachol injected into the lateral cerebral ventricle (i.c.v.), the electrical stimulation of and carbachol-induced stimulation of, the central nucleus of the amygdala were investigated in conscious, unrestrained Sprague-Dawley rats. I.c.v. and intra-amygdalar carbachol caused a significant rise in blood pressure of 22.9 +/- 2.8 and 16.8 +/- 2.2 mmHg, respectively. Electrical stimulation (1 ms; 80 Hz, 50-300 mu A, for 30 s) of the central nucleus of amygdala also produced intensity-dependent presser effects. Electrolytic lesion of the AV3V region abolished the presser responses induced by carbachol and by electrical amygdala stimulation. The heart rate changes were also significantly inhibited in the AV3V-lesioned rats. These results indicate that the integrity of the AV3V region is essential for the central cholinergic cardiovascular changes induced by central amygdaloid nucleus stimulation. (C) 1997 Elsevier Science B.V.
Keywords: amygdala; AV3V region; cholinergic hypertension; carbachol; blood pressure; heart rate; NUCLEUS TRACTUS SOLITARII; CENTRAL NERVOUS-SYSTEM; CHOLINERGIC MECHANISMS; NATRIURETIC RESPONSES; MUSCARINIC RECEPTORS; HEMORRHAGIC-SHOCK; HYPERTENSIVE RAT; LESIONS; AREA; BRADYCARDIA